Annual Report, Autumn Equinox 1992 ce. - Rowan Tree Church (Northridge, CA: Rowan Tree Church, 1992)
The tenth Annual Report provides detailed descriptions of each of the “Communities” that are part of the Rowan Tree Church, including those involved in their organization and the number of members for each Community. Changes in the RTNews are discussed at length and the moving away from a publications sent free to all members. Mention of the Rowan Tree Quarterly reinstatement, and The Littlest Unicorn woes are also mentioned. The treasurer's report states the need for better communication regarding how the Rowan Tree Church’s finances are handled. The stability of the Mystery School is also expressed.
This digital asset was created from the original digital scans by Rev. Paul V. Beyerl and provided to the Valdosta State University, Archives & Special Collections to be part of their Rowan Tree Church Periodicals Collection of the New Age Movements, Occultism, and Spiritualism Research Library. The Rowan Tree Church is an earth-based religion founded by Rev. Paul Beyerl, a Third Degree Initiate in the Alexandrian Tradition of Wicca, and incorporated on February 4, 1980 in Minneapolis, Minnesota. The church is now based in Kirkland, Washington with many communities throughout the United States and Canada. The roots of the Church extend back to 1976 which Rev. Beyerl began teaching Wicca, Astrology, and Herbalism out of his home. The Church's religion, The Tradition of Lothloriën, embraces inclusiveness and accepts all people regardless of faith, sexual orientation, race, or gender, a noted departure from early Alexandrian Wicca. The Tradition has elements of Herbalism, Astrology and Tibetan Buddhism in its structure, and is deeply rooted in its Mystery School, an in-depth study program that leads to Ordination, and the Hermit's Grove, its educational and publishing entity. Noted publications are The Unicorn, The Littlest Unicorn for children, and The Hermit’s Lantern.
Keywords: Rowan Tree Church--History; Rowan Tree Church--Appropriations and expenditures; Lothloriën (Wiccan sect); Mystery School of Lothloriën; Wicca--Study and teaching; Littlest Unicorn (Rowan Tree Church); Galadhrim Society; Prison Outreach Program; Annual reports